Evaluasi Kebijakan Pendidikan Melalui Sistem Zonasi Di Indonesia - Indah Wahyu Maesarini; Samsudin Samsudin (Jurnal Ilmu Administrasi Publik, 2023)
The zoning system is still a mainstay in implementing student admissions in Indonesia. It cannot be denied that this zoning system gives hope to the community that it will be easier to get a decent school based on where the students live. The reality in the field shows the tendency for malpractice and maladministration to occur from the implementation of the zoning system, where the zoning system becomes an opening for fraudulent actions by a number of individuals who take advantage of the weaknesses of this system. This existing condition requires immediate handling through an evaluation of the existing zoning system implementation policy. By using the concept of public policy evaluation and literature studies, it was found that there are 4 things that need to be considered in carrying out evaluations on the implementation of zoning system policies, including: explanation, audit compliance, and accounting. Future suggestions require a unified perception of the importance of changing the stigma of favorite schools by opening more state schools to avoid thinking that the school is the best among the best. Officer compliance with controlling existing implementation is carried out in conjunction with evaluation of findings in the field for future improvements. The availability of an audit function is important as the final bulwark for punishment of violations in the field through firm action.